Gastrointestinal, metabolic, and nutritional disorders: A plant-based ethnoveterinary meta-analysis in the Catalan linguistic area - Cáceres, Fuencisla; Vallès, Joan; Garnatje, Teresa; Parada, Montse; Gras, Airy (Frontiers in Veterinary Science, 2022)
Veterinary care is fundamental for animal wellbeing, and so is achieving a comprehensive understanding of traditional ethnoveterinary applications. However, little attention has been paid to it so far in industrialized countries, and in particular in Western Europe. In this context, the present work aims to make a contribution to this issue in the Catalan linguistic area, focusing on the study of plants used, at a popular level, to treat and deal with gastrointestinal, metabolic, and nutritional disorders, which are among the most important issues that affect animals. Data obtained in this study come from the popular knowledge about plants for veterinary purposes from 599 informants, who jointly provided 1,405 reports of use from 148 plant taxa. The most cited species have been Tanacetum parthenium (L.) Sch.Bip. (9.04%), Olea europaea L. subsp. europaea var. europaea (6.26%), and Euphorbia lathyris L. (6.26%). At higher taxonomic levels, the botanical families with more ethnoveterinary applications were Asteraceae (24.48%), Euphorbiaceae (8.33%), and Oleaceae (7.12%). Among the total use reports, 95.02% refer to disorders of the gastrointestinal system, 4.34% to nutritional disorders, and 0.64% to metabolic disorders. Antidiarrheal (18.01%), digestive (16.51%), and laxative (15.80%) have been the most reported veterinary uses. The most used plant parts have been the aerial part (40.50%), the fruit or the infructescence (18.65%), and the flower or inflorescence (16.01%). The main preparation and administration forms reported were tisane (58.69%), followed by direct use (without any specific pharmaceutical form; 21.77%). The global corpus of ethnoveterinary knowledge for the gastrointestinal system disorders in the territory of study is diverse, with some species having a very high cultural value, as indicated by an informant consensus factor very close to 1. Some reported uses were also confirmed after consultation of encyclopedic pharmacological works, although few of these works are specifically devoted to veterinary uses. The results of this study are relevant to preserve the ethnoveterinary knowledge, but also represent an important contribution to be taken into account in research for future development of new plant-based drugs for animals.